2014
DOI: 10.5603/fhc.2014.0021
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of human gastric adenocarcinoma partly depends on phosphoinositide-specific phospholipase γ1 expression

Abstract: Abstract:It is known that phosphoinositide-specific phospholipases g1 (PLCg1) can trigger several signalling pathways to regulate cell proliferation, differentiation, and metastasis. However, whether this kinase is highly expressive and active in human gastric adenocarcinomas, and whether it can play an important role in the development of the cancer, have not yet been investigated. The aim of the study was to investigate the expression of PLCg1 in human gastric adenocarcinoma, while the question of whether PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…After cells were tranduced with the different shPLCγ1 vectors by a lentiviral transfection strategy, stable cell lines were obtained under the pressure of puromycin (2 μg/mL, BioVision, Inc., Milpitas, CA, USA). In addition, cells were transiently transfected for 24 hours with pRK5-HA-PLCγ1 (pRK5-PLCγ1) vector expressing PLCγ1, p3xFLAG-CMV10-AMPKα1 (AMPKα1) vector expressing AMPKα1, p3xFLAG-CMV10-AMPKα2 (AMPKα2) vector expressing AMPKα2, using Lipofectamine 3000 (Invitrogen, Carlsbad, CA, USA), following the manufacturer's procedure and previous studies [9,41].…”
Section: Plasmid Construction and Transfectionmentioning
confidence: 99%
See 3 more Smart Citations
“…After cells were tranduced with the different shPLCγ1 vectors by a lentiviral transfection strategy, stable cell lines were obtained under the pressure of puromycin (2 μg/mL, BioVision, Inc., Milpitas, CA, USA). In addition, cells were transiently transfected for 24 hours with pRK5-HA-PLCγ1 (pRK5-PLCγ1) vector expressing PLCγ1, p3xFLAG-CMV10-AMPKα1 (AMPKα1) vector expressing AMPKα1, p3xFLAG-CMV10-AMPKα2 (AMPKα2) vector expressing AMPKα2, using Lipofectamine 3000 (Invitrogen, Carlsbad, CA, USA), following the manufacturer's procedure and previous studies [9,41].…”
Section: Plasmid Construction and Transfectionmentioning
confidence: 99%
“…Cells were seeded in 96-well plates and each well contained 100 μL of complete growth medium and cultured for the indicated time. The number of viable cells were measured by 3-(4, 5-Dimethylthiazol-2-y)-2,5-diphenyl-tetrazolium bromide (MTT) assay as described as previous studies [9,42].…”
Section: Mtt Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…PLCγ mediates high levels of glucose and insulin-induced cell proliferation and migration in MDA-MB-468 breast cancer and SW480 colon cancer cells in vitro [ 8 ]. Our previous study also showed the higher expression of PLCγ1 in human gastric adenocarcinoma tissue and that the metastasis of human gastric adenocarcinoma cells partly depends on PLCγ1 expression [ 9 ]. Moreover, it has been shown that the depletion of PLCγ expression or inhibition of its activity not only significantly increases cisplatin-induced apoptosis but also suppresses the invasive ability of RhoGDI2-overexpressing SNU-484 gastric cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%